2005
DOI: 10.1016/j.rapm.2004.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia after arthroscopic rotator cuff repair: Subacromial versus interscalene continuous infusion of ropivacaine

Abstract: After arthroscopic rotator cuff repair, continuous interscalene block provides better analgesia compared with continuous subacromial infusion but with an increased incidence of minor side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
3
36
0
2
Order By: Relevance
“…5,6 Notwithstanding their analgesic efficacy, however, these methods present procedural difficulties and are accompanied by complications inherent in their invasive nature. 7 Among the noninvasive methods to control postoperative pain, intravenous opioid-based patientcontrolled analgesia (IV-PCA) has been widely accepted as effective and safe.…”
Section: Résumémentioning
confidence: 99%
“…5,6 Notwithstanding their analgesic efficacy, however, these methods present procedural difficulties and are accompanied by complications inherent in their invasive nature. 7 Among the noninvasive methods to control postoperative pain, intravenous opioid-based patientcontrolled analgesia (IV-PCA) has been widely accepted as effective and safe.…”
Section: Résumémentioning
confidence: 99%
“…The single local anaesthetic injection effectiveness for open shoulder surgery was previously poorly documented and not well defined [2,8,14], more data even if with discordant results have been reported that however were more related to the continuous infusion of anaesthetics and arthroscopic setting [5,9,[15][16][17]. Anyhow, a little clinical benefit of local infiltration was evidenced [3].…”
Section: Discussionmentioning
confidence: 99%
“…Discordant results have been reported regarding local injection of anaesthetics in the intra-articular region for control of postoperative pain after shoulder surgery [3,8], similar to subacromial injection [5,9,10] and block of the suprascapular nerve [11].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although these benefits are generally limited to the day of surgery, they nevertheless represent a valuable alternative to general anesthetic and postoperative opioid techniques. [1][2][3][4] Furthermore, limited comparative studies have shown that an interscalene or suprascapular block provides better analgesia than does an intra-articular injection or infusion of local anesthetic 5,6 and without any risk for chondrolysis. Continuous perineural catheter techniques provide superior analgesia for total shoulder arthroplasty and various ambulatory shoulder surgeries.…”
mentioning
confidence: 99%